Estrategias metodológicas centradas en el aprendizaje colaborativo. - Celi Paz, Carmen María (2018)
The educational processes at the universities have been objet of debates relationed with teachers formation, who have been criticized by the lack of their didactic and profesional competences to get expected learnings. The absense of collaborative methodological strategies application carries out to preserve traditional schemes. The teacher as a profesional has the obligation to promote the integral development of the future generations, thus his own formation should provide habilities and knowledgements to understand the student as an the active and complex subject in order to improve his skills and habilities. In this sense Basic education major´s teachers don´t consider the student like the center of the teaching process. Therefore the developed methodologies have placed the teacher as the main actor of the process rather than the student, who became a receptor of knowledgent rather than a builder of it. This tradictional model based on the expositive class has been the main focus for the learning and it hasn´t diversified the use of methodological strategies. This research aims to describe the methodological strategies used by teachers in the Basic Education major at Cotopaxi Technical University and its relation with the the colaborative learning development. The methodology applied was based on the quantitative approach, the methods used were deductive an inductive, bibliographic and research field to describe about teaching and collaborative learning methodologies. The techniques were the interview and survey, which permited to collect information to autorities, teachers and students about the problema of the investigation. The collected information permited to stablish characteristics of traditional and innovating teaching, although the traditional is predominant, teacher is the center of the process and there isn´t any student´s participation. The techniques used were the interview and survey, which allow collecting information from authorities, teachers and students about the problem studied in this research. The data collected allowed identifying traditionalist teaching and innovative practices. However, there is a presence of expositive class, which focused the teaching process in the educator, leaving aside the participation of students in this process. In addition, it found some constraints in the implementation of strategies of collaborative learning, the lack of planning and teaching control in all stages of the process of collective construction of learning, the lack of responsibility and commitment of students to assume new roles to transform teaching and learning processes. For that, it is required to build teachers and students´ attitudinal change to achieve an integral formation of the future teachers of the country basedon the collective learning building.